2022
DOI: 10.1029/2021gh000521
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Meteorological Variables and Aerosols in the Transmission of COVID‐19 During Harmattan Season

Abstract: The outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), originating from the Wuhan region of China, has caused devastating damages across the world. The impact of SARS-CoV-2 (COVID-19) has been reported in global transportation (Abu-Rayash & Dincer, 2020) and power system (Gulati et al., 2021). The greatest impact has been on the global health system, overwhelming the health care facilities of many developed and developing countries (Armocida et al., 2020). COVID-19 infections could be as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 58 publications
(65 reference statements)
1
18
0
1
Order By: Relevance
“…The increase in PM from January to March can be associated with tiling of land, bush burning as farmer will be getting their land ready for farming as we approach rainy season and this is in line with the study reported by Abulude & Abulude (2021) and Ogunjo et al (2022). The decrease in PM from May to October can be trace to wet season as precipitation helps to lower the amount of PM in the atmosphere as the particles drop together with rain to the ground.…”
Section: Monthly Variationsupporting
confidence: 85%
See 2 more Smart Citations
“…The increase in PM from January to March can be associated with tiling of land, bush burning as farmer will be getting their land ready for farming as we approach rainy season and this is in line with the study reported by Abulude & Abulude (2021) and Ogunjo et al (2022). The decrease in PM from May to October can be trace to wet season as precipitation helps to lower the amount of PM in the atmosphere as the particles drop together with rain to the ground.…”
Section: Monthly Variationsupporting
confidence: 85%
“…Harmattan is a cool, dry breeze that sweeps from the northeast or east across the Western Sahara. Up to half of the world's substantial dust emissions come from the Sahara Desert (Ogunjo et al, 2022). Generally it has been reported that in Nigeria the rainy season falls between the months of April through October and the dry season in between November through March Akpootu et al, 2019a) Kano state (Latitude: 12° 40′ and 10° 30′N, and longitude: 7° 40′ and 9° 30′ E).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, adequate characterization of the energy systems' performance during the pandemic is needed to successfully drive post-pandemic recuperation and to better manage similar events in the future. Different studies highlight a reduction in the hourly energy demand at the local level, while higher consumption moved from the productive and commercial sectors to households [153][154][155]. In the Iberian Peninsula (i.e., at national scale), the average consumption reduced by 12% to 17% affecting the electricity market [156].…”
Section: Clean Energy and Responsible Consumption And Productionmentioning
confidence: 99%
“…In a study of 20 countries, meteorological factors have been adjudged to be good predictors of COVID‐19 cases based on the Granger causality test (Mirri et al., 2021 ; Sarkodie & Owusu, 2020 ). Atmospheric parameters such as temperature and humidity have been found to play important role in the transmission of COVID‐19 within Nigeria (Ogunjo, Olaniyan et al., 2022 ). It is clear from previous and relevant studies that weather parameters may have associations with COVID‐19 cases and that variation in transmission and death tolls are not uncommon in different regions; thus, a few more local/regional studies may not only help in consolidating the impact of climatic patterns from the less reported countries and localities, for instance, South Africa, but also serve as a useful stepping stone to further research though not without its challenges.…”
Section: Introductionmentioning
confidence: 99%